2021
DOI: 10.1039/d1nr04672a
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent twist-bend coupling in DNA minicircles

Abstract: Sequence-dependent coupling between DNA bending and its helical twist in DNA minicircles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The poloidal rotation occurs very rapidly as shown by the sudden changes in the poloidal angle by more than 200° within 100–200 ns. In our previous work, 26 we observed that the poloidal rotation is ceased when a structural defect called the kink occurs. Therefore, the continuous variation of the poloidal orientation in Figure 2a suggests that the DNA minicircle remains stable for 5 μs without any structural defect.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The poloidal rotation occurs very rapidly as shown by the sudden changes in the poloidal angle by more than 200° within 100–200 ns. In our previous work, 26 we observed that the poloidal rotation is ceased when a structural defect called the kink occurs. Therefore, the continuous variation of the poloidal orientation in Figure 2a suggests that the DNA minicircle remains stable for 5 μs without any structural defect.…”
Section: Resultsmentioning
confidence: 91%
“…26 Here, we investigated internal dynamic of a DNA minicircle with the sequence of (AT) 45 /(AT) 45 by extending previous MD simulation duration to 5 μs. 26 In our previous work, the focus was entirely on the coupling between DNA bending and its helical twist, not the dynamics of DNA minicircles. Although the time correlation function (TCF) for the poloidal rotation was calculated, the result was discussed to justify the length of the MD simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that such low-temperature processes for deposition and annealing under 400 °C are sufficient to crystallize HZO films. [42][43][44]. Therefore, it will be compatible with TFT technologies.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Third, instead of injecting RNA-based therapeutics directly into the brain in preclinical models, researchers are encouraged to test clinically relevant routes of administration for ncRNA treatments. For example, multiple studies have demonstrated the promise of intranasal administration as a way to bypass the blood-brain barrier ( 196 , 197 , 231 , 248 253 ). Intrathecal injections of modified ASOs and siRNAs and nanoparticle-containing nucleic acids have also achieved high brain uptake in preclinical and clinical studies ( 131 , 200 , 254 ) and should also be employed in SUD experiments.…”
Section: Ongoing Challenges and Outlookmentioning
confidence: 99%